Systematic Literature Review on Scientific Argumentation Models in Chemistry Education and Their Relevance to the Sustainable Development Goals - Gesa Salutri; A. K. Prodjosantoso; Dewi Vitama Pusfitasari (Universitas Syiah Kuala, 2026)
Scientific argumentation is one of the key skills in 21st-century learning that plays a role in developing students’ critical thinking, scientific communication, and conceptual understanding. In chemistry education, scientific argumentation is particularly important because chemical concepts are often abstract and require evidence-based reasoning. This study aims to identify models of scientific argumentation used in chemistry education, analyze the chemical topics examined, evaluate the resulting learning outcomes, and examine their relevance to the sustainable development goals (SDGs). The method used is a systematic literature review (SLR) following the PRISMA guidelines. Articles were obtained from the scopus, ERIC, and google scholar databases for the years 2015–2025. Based on the selection process, 20 articles meeting the inclusion criteria were identified. The findings indicate that argument-driven inquiry (ADI) is the most widely used model, followed by socio-scientific issues (SSI) and inquiry-based learning. The most dominant topics were organic chemistry, chemistry laboratories, general chemistry, and sustainability/ environmental chemistry. Scientific argumentation-based learning was proven to enhance students’ argumentation skills, critical thinking, scientific communication, conceptual understanding, and scientific attitudes. Furthermore, various studies demonstrate a strong connection to SDG 4 (quality education), SDG 6 (clean water and sanitation), SDG 7 (affordable and clean energy), SDG 12 (responsible consumption and production), and SDG 13 (climate action). However, explicit integration between scientific argumentation, the SDGs context, and the development of scientific attitudes remains limited. Therefore, further research is needed to integrate ADI, the SDGs, and scientific attitudes into chemistry education